Spatially consistent imputations of forest data under a semivariogram model - Strîmbu, Victor Felix; Ene, Liviu Teodor; Næsset, Erik (Canadian journal of forest research, 2016)
This study proposes a method to perform spatially consistent imputations of forest data to serve simulation studies where spatial autocorrelation is expected to have an effect (e.g., sampling simulations and forest scenario analysis). Starting with a nearest neighbour imputation, an optimization process brings the spatially comprehensive data to a desired state, controlled by a target semivariogram and a target histogram. The target values for both parameters may be approximated using empirical data and are combined in the objective function used by the optimization algorithm. Here, we demonstrate a case study using wall-to-wall airborne laser scanner data, satellite data, and field observations for an 852 ha forest area in southern Norway. Different combinations of data types and target parameters were tested, and the target values were reached in most cases. In some cases, with a more restrictive objective function, the semivariogram did not completely converge to its target values, yet still had a convergence of at least 93%, expressed by the difference reduction between initial and target values. The results recommend the proposed method as a practical means to generate spatially explicit forest data when a particular distribution and well-defined spatial dependence are required.